Peran Perempuan Dalam Penyebaran Dan Pengajaran Hadits di Madrasah Hadits Klasik - Iis Siti Nurlatifah; Engkos Kosasih; Isra Mardi (Cakrawala: Journal of Religious Studies and Global Society, 2025)
Women have made significant contributions to the dissemination and teaching of hadith, particularly in classical hadith schools that emerged during early Islam. Their roles extended beyond narration to include teaching and the development of hadith sciences. This article aims to explore the role of women in this context, highlighting key figures such as Aisyah bint Abu Bakr, Ummu Salamah, Fatimah al-Marwazi, and Karimah al-Marwazi. The study employs a descriptive-analytical method based on library research, referencing primary sources like classical hadith compilations and secondary sources from academic articles. The findings reveal that women played strategic roles in the transmission and teaching of hadith. Aisyah, for instance, narrated over 2,000 hadiths and became a central reference in various aspects of Islamic jurisprudence. Female scholars like Fatimah al-Marwazi and Karimah al-Marwazi significantly contributed by teaching monumental works such as Sahih Bukhari in classical hadith schools. Despite social and cultural challenges, these women successfully left a lasting impact on the development of Islamic scholarship, which remains influential today.